2022
DOI: 10.3389/fmed.2022.936126
|View full text |Cite|
|
Sign up to set email alerts
|

Three-Month Follow-Up of Heterologous vs. Homologous Third SARS-CoV-2 Vaccination in Kidney Transplant Recipients: Secondary Analysis of a Randomized Controlled Trial

Abstract: Response to SARS-CoV-2-vaccines in kidney-transplant recipients (KTR) is severely reduced. Heterologous3rd vaccination combining mRNA and vector vaccines did not increase seroconversion at 4 weeks after vaccination, but evolution of antibody levels beyond the first month remains unknown. We have recently completed a randomized-controlled trial on heterologous (Ad26COVS1) vs. homologous (BNT162b2 or mRNA-1273) 3rd vaccination in 201 KTR not developing SARS-CoV-2-spike-protein antibodies following two doses of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The increase in KTRs displaying neutralizing antibody activity against the Omicron variant from 6 of 45 (13%) at t1 to 10 of 45 (22%) at t2 in our study cohort was striking, although not significant. Notably, other studies have also observed delayed immune responses, with Heinzel et al 21 observing an increase in antispike IgG antibodies in 8% of 169 assessed KTRs from 1 to 3 mo after a third COVID-19 vaccination. In addition, Ronicke et al 22 reported increasing antispike S1 IgG levels in 26 of 148 seroconverted KTRs (18%) comparing antibody levels at 1 mo with levels at 2 and 4 mo after at least 1 COVID-19 vaccination and demonstrated that MPA intake led to delayed immune responses.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in KTRs displaying neutralizing antibody activity against the Omicron variant from 6 of 45 (13%) at t1 to 10 of 45 (22%) at t2 in our study cohort was striking, although not significant. Notably, other studies have also observed delayed immune responses, with Heinzel et al 21 observing an increase in antispike IgG antibodies in 8% of 169 assessed KTRs from 1 to 3 mo after a third COVID-19 vaccination. In addition, Ronicke et al 22 reported increasing antispike S1 IgG levels in 26 of 148 seroconverted KTRs (18%) comparing antibody levels at 1 mo with levels at 2 and 4 mo after at least 1 COVID-19 vaccination and demonstrated that MPA intake led to delayed immune responses.…”
Section: Discussionmentioning
confidence: 95%
“…KTRs receiving immunosuppressive therapy are at higher risk for poor COVID-19-related outcomes and therefore in urgent need for establishing a vaccine-induced SARS-CoV-2-specific humoral and cellular immune response to prevent severe COVID-19 (15,(36)(37)(38). Immunosuppressive therapies could hinder (19,37) and the administration of different vaccine regimens could influence the development of vaccine-induced immune responses in KTRs. As a consequence, close vaccine-accompanying immune monitoring is highly recommended for KTRs to assess the vaccination effectiveness (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…First, several immunosuppressed patients are found to have a decreased humoral vaccination response (14)(15)(16). Second, other arms of the adaptive immune response are not always considered, and the emerging data so far show an inconsistent picture (17)(18)(19). Due to the lower response to the vaccine, more severe courses of COVID-19 and increased mortality are currently found in immunosuppressed patients, even if the overall mortality has been significantly lower as compared to the infection with the delta variant (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…We identified 2 RCTs, 8 non-randomiz studies comparing interventions and 27 prognostic studies without a control ar Twenty-six studies investigated a study population containing seropositive KTRs af their previous vaccination series . Eight studies included only seronegative KT [47][48][49][50][51][52] and three studies included only KTRs with low or no previous seroconvers [53][54][55].…”
Section: Description Of Studiesmentioning
confidence: 99%